Percutaneous Spinal Cord Stimulation for Failed Back Surgery Syndrome: A Retrospective Study - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2020)
AIM: To evaluate the outcomes of percutaneous spinal cord stimulation (PSCS) in patients with failed back surgery syndrome (FBSS) in an academic tertiary care center. MATERIAL and METHODS: The hospital records of patients with FBSS who had undergone PSCS were retrospectively reviewed. A total of 19 patients with FBSS matched the search criteria, and among them, 16 were included in the study, in whom permanent implantable pulse generators (IPGs) were implanted. Demographic, clinical and surgical outcomes were evaluated. RESULTS: Twelve (75%) women and 4 (25%) men with a median age of 50 years (range, 35-80 years) were analysed. The average number of surgeries before PSCS was 1.6 +/- 1.2 (range, 1-4). Pain was localised in the back and leg in 81.25% of the patients. The mean duration of symptoms was 6.3 +/- 3.1 years (range, 2-10 years). The mean length of trial period was 16.3 +/- 6.8 days (range, 7-29 days). In this study, the permanent implantation rate was 84.2% (16/19). The mean follow-up time was 18.3 +/- 3.9 months (range, 14-26 months). Postoperative back/leg numerical pain rating scale (NPRS) score was significantly lower than preoperative back/leg NPRS score (p<0.001). The postoperative Oswestry Disability Index (ODI) score was significantly lower than the preoperative ODI score (p<0.001). CONCLUSION: PSCS is a safe and effective treatment method for patients with FBSS. In this study, the high rate of improvement in the outcome scores may be attributed to the small sample size and early PSCS implantation.
Keywords: Failed back surgery syndrome; Chronic pain; Spinal cord stimulation; Minimally invasive surgery; CHRONIC PAIN; NEUROPATHIC PAIN; PADDLE LEAD; LEG PAIN; MANAGEMENT; COMPLICATIONS; EXPERIENCE